Isoscapes Understanding movement, pattern, and process on Earth through isotope mapping - West, Jason B.; Bowen, Gabriel J.; Dawson, Todd E.; Tu, Kevin P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Stable isotope ratio variation in natural systems reflects the dynamics of Earth systems processes and imparts isotope labels to Earth materials. Carbon isotope ratios of atmospheric CO2 record exchange of carbon between the biosphere and the atmosphere; the incredible journeys of migrating monarchs is documented by hydrogen isotopes in their wings; and water carries an isotopic record of its source and history as it traverses the atmosphere and land surface. Through these and many other examples, improved understanding of spatio-temporal isotopic variation in Earth systems is leading to innovative new approaches to scientific problem-solving. This volume provides a comprehensive overview of the theory, methods, and applications that are enabling new disciplinary and cross-disciplinary advances through the study of "isoscapes": isotopic landscapes. "This impressive new volume shows scientists deciphering and using the natural isotope landscapes that subtly adorn our spaceship Earth." Brian Fry, Coastal Ecology Institute, Louisiana State University, USA "An excellent timely must read and must-have reference book for anybody interested or engaged in applying stable isotope signatures to questions in e.g. Anthropology, Biogeochemistry, Ecology, or Forensic Science regarding chronological and spatial movement, changes, or distribution relating to animals, humans, plants, or water." Wolfram Meier-Augenstein, Centre for Anatomy & Human Identification, University of Dundee, UK "Natural resources are being affected by global change, but exactly where, how, and at what pace? Isoscapes provide new and remarkably precise answers." John Hayes, Woods Hole Oceanographic Institution, USA "This exciting volume is shaping a new landscape in environmental sciences that is utilizing the remarkable advances in isotope research to enhance and extend the capabilities of the field." Dan Yakir, Weizmann Institute of Science, Israel
Gathering and Using Spatially Explicit Isotope Data -- Global Network Measurements of Atmospheric Trace Gas Isotopes -- Global Hydrological Isotope Data and Data Networks -- Remote Sensing of Nitrogen and Carbon Isotope Compositions in Terrestrial Ecosystems -- Novel Approaches for Monitoring of Water Vapor Isotope Ratios: Plants, Lasers and Satellites -- Applications of Stable Isotopes for Regional to National-Scale Water Quality and Environmental Monitoring Programs -- Environment in Time and Space: Opportunities from Tree-Ring Isotope Networks -- Isotope Mapping: Theory and Mathods -- Statistical and Geostatistical Mapping of Precipitation Water Isotope Ratios -- Approaches to Plant Hydrogen and Oxygen Isoscapes Generation -- Continental-Scale Distributions of Vegetation Stable Carbon Isotope Ratios -- Comprehensive Dynamical Models of Global and Regional Water Isotope Distributions -- Using Nitrogen Isotope Ratios to Assess Terrestrial Ecosystems at Regional and Global Scales -- Using Isoscapes to Model Probability Surfaces for Determining Geographic Origins -- Multidisciplinary Applications of Isotopes -- Using Isoscapes to Track Animal Migration -- Using Isoscapes to Trace the Movements and Foraging Behavior of Top Predators in Oceanic Ecosystems -- Toward a ?13C Isoscape for Primates -- Stable and Radiogenic Isotopes in Biological Archaeology: Some Applications -- A Framework for the Incorporation of Isotopes and Isoscapes in Geospatial Forensic Investigations -- Stable Isotopes in Large Scale Hydrological Applications -- The Carbon Isotope Composition of Plants and Soils as Biomarkers of Pollution -- Isoscapes in a Rapidly Changing and Increasingly Interconnected World.
Keywords: Environmental sciences; Geography; Ecology; Anthropology; Environment; Geoecology/Natural Processes; Environment, general; Ecology; Earth Sciences, general; Anthropology